Intravenous Tranexamic Acid Improves the Intraoperative Visualization of Endoscopic Sinus Surgery for High-Grade Chronic Rhinosinusitis: A Randomized, Controlled, Double-Blinded Prospective Trial - Wenjing Yang (Frontiers Media S.A., 2021)
Objective: Intraoperative bleeding during endoscopic sinus surgery (ESS) for high-grade rhinosinusitis can be serious and can further obscure the surgical field. This study was designed to evaluate the effect of tranexamic acid (TXA) on the surgical visualization of ESS for high-grade rhinosinusitis.Methods: In total, 60 patients with high-grade chronic rhinosinusitis (Lund-Mackay score 12 or greater) treated by ESS were randomized into two groups: the control group (Group C) or the TXA group (Group T). Each group included 30 patients. Patients in Group T received intravenous TXA, and those in Group C received normal saline. The Boezaart grading scale (BS) score was assessed as the primary outcome. Total blood loss (TBL), whole blood coagulation, and fibrinolysis were assessed by Sonoclot analysis, and complications were recorded and compared between the groups.Result: A significant difference was found in the BS score between Group T and Group C [2.02 (1.88–2.05) vs. 2.27 (2.13–2.41), P = 0.011]. Increases in platelet function (PF) and fibrin degradation time (FDT) were assessed during the operation and showed significant differences between Group T and Group C (P = 0.040 for PF; P = 0.010 for FDT). No difference in complications was found between the two groups.Conclusion: A 15 mg/kg bolus of intravenous TXA before surgery can improve the surgical visualization of ESS for high-grade chronic rhinosinusitis without causing significant adverse effects. Intravenous TXA may be beneficial in ESS for high-grade chronic rhinosinusitis.Clinical Trial Registration:https://www.chictr.org.cn/edit.aspx?pid=121653&htm=4.